Dysphagia in an elderly woman with diabetes mellitus: What is your call? - Pazhanivel Mohan; Malathi Munisamy (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Mohan P, Munisamy M. Dysphagia in an elderly woman with diabetes mellitus: What is your call? Turk J Gastroenterol 2020; 31(8): 607.